The Effect Of Tax Socialization And Tax Sanctions On Taxpayer Compliance (Study on E-Commerce in Majalengka Regency) - Yogi Ginanjar; Raden Wulan Saparinda Wulan (Institute of Computer Science (IOCS), 2022)
Tax revenue in Indonesia is still very far from planning . There are several things that make taxpayer compliance low, including the many cases of tax evasion to tax bribery, so that in these conditions it greatly affects taxpayer compliance. This study aims to determine the effect of tax socialization and tax sanctions on taxpayer compliance in E-Commerce in Majalengka Regency. The population in this study is MSME E-Commerce in Majalengka Regency. The sampling technique used in this study is probability sampling using simple random sampling where in determining the sample at random, the number of samples in this study is 100 respondents. Testing of research instruments is done by testing the validity and reliability. The data analysis technique uses descriptive analysis and verification through classical assumption test, multiple linear regression analysis, determination analysis, model feasibility test (F test) and hypothesis testing with t test.analytical tool in this study uses the SPSS 25 program. The results show that tax socialization affects taxpayer compliance and tax sanctions affect taxpayer compliance.